Human-Rights-Based Assessment Tool for Country-Level Grievance Mechanisms - World Bank (Washington, DC : World Bank, 2022)
The assessment tool is presented in five sections: (i) General Information about the Grievance Mechanism collects basic information about the responding agency and the environment in which its GM operates; (ii) GM Design and Communications examines the effectiveness of the provision of information about the GM, its procedures, the user-centricity of grievance uptake channels, the extent to which the needs of vulnerable groups are considered, and if confidentiality and anonymity for complainants are guaranteed; (iii) Grievance Handling and Resolution looks at the processes in place to acknowledge, log, categorize, and resolve grievances, and how well different enablers, such as a strong customer service culture, standardized processes, interagency/interinstitutional cooperation, and capacity building serve the organization’s purpose; (iv) Monitoring and Evaluation explores the depth and systematic character of data collection about complainants’ satisfaction levels, user demographics, and complaint resolution, as well as the extent to which these data are publicly communicated; (v) GM Strengths and Areas for Improvement invites a strategic reflection on the GM’s strengths and weaknesses, as well as opportunities for its improvement. Its unscored, open-ended questions are intended to encourage bigger picture reflection and to prompt a discussion on further actions that can be taken in the future to bring the GM to the next level, possibly with external support.